THE REPRESENTATION OF WOMAN AS FEMME FATALE IN ROALD DAHL'S LAMB TO THE SLAUGHTER - Hanum Bella Ardya Garini; Winarti Winarti (Universitas Duta Bangsa Surakarta, 2021)
The purpose of this study is to know the representation of woman as femme fatale in Lamb to the Slaughter. The research methods of this study is a qualitative research method. The primary source of data is the Lamb to the Slaughter short story, and the secondary source of the data is the main character Mary Malony. The result of this study shows that Mary became as a femme fatale is actually triggered by the conflict that occur between her and her husband. Knowing the fact that her beloved husband asks for a divorce when she is pregnant is not the right time. Mary, who is originally an innocent and normal wife, suddenly turns into a dangerous woman.